The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7759/cureus.9468
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Emergency Department Presentations due to Injuries From Motor Vehicle Crashes and Pedestrian Strikes

Abstract: Objective The objective of this study was to analyze the causes and outcomes of presentations to the emergency department (ED) due to injuries from motor vehicle crashes and pedestrian strikes along several parameters. Methods Data from 798 patients who were injured due to motor vehicle crashes or pedestrian strikes that occurred in Canakkale Province were retrospectively analyzed. Patient demographic data such as age and gender, emergency service outcomes, and the consulted clinics were also recorded. Distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…According to a study conducted at Canakkale Province (Turkey), numerous patients were referred to other specialities, with the highest referrals to orthopaedics, 14.8 % (n=118), neurosurgery 8.1 % (n=65), and thoracic diseases 2.3 % (n=18) clinics amongst many other specialities such as general surgery, plastic surgery unit and the cardiovascular unit, etc. [21] The referral rate in this configuration was 61% (n=307).…”
Section: Association Between Experiencing Pain and The Sex Of The Patient And Desire To Pursue Legal Actionmentioning
confidence: 87%
See 1 more Smart Citation
“…According to a study conducted at Canakkale Province (Turkey), numerous patients were referred to other specialities, with the highest referrals to orthopaedics, 14.8 % (n=118), neurosurgery 8.1 % (n=65), and thoracic diseases 2.3 % (n=18) clinics amongst many other specialities such as general surgery, plastic surgery unit and the cardiovascular unit, etc. [21] The referral rate in this configuration was 61% (n=307).…”
Section: Association Between Experiencing Pain and The Sex Of The Patient And Desire To Pursue Legal Actionmentioning
confidence: 87%
“…In comparison to other road users, the inherent nature of a pedestrian's direct exposure to a collision created an additional risk factor for suffering more severe injuries. [21] Only 15% (n=73) of patients sustained non-grievous injuries, while the remainder sustained injuries classified as grievous or above under the Sri Lankan Penal Code.…”
Section: Association Between Experiencing Pain and The Sex Of The Patient And Desire To Pursue Legal Actionmentioning
confidence: 99%
“…In 2021, the United States saw 2.5 million people injured in MVAs and 42,939 deaths associated with MVAs [ 5 ]. This prevalence has led to a substantial burden on emergency services, not only in the U.S. but globally [ 6 ]. Therefore, it is imperative to develop sustainable analyses of injury severity and overall clinical courses of both drivers and passengers after MVAs to find patterns and ensure more efficient, effective care.…”
Section: Discussionmentioning
confidence: 99%
“…►Table 3 summarizes the different studies in this context that came up with contrasting findings and conclusions. [21][22][23][24][25][26] The number of persons injured by traffic accidents was slightly higher during Ramadan than in other months in Al Ain, UAE. Most of the accidents and injuries occurred from 8.00 a.m. to 2.00 p.m. 21 However, Mehmood et al found that the frequency of road traffic crashes did not change significantly during Ramadan when studying road traffic data in Karachi in Pakistan for 2006 and 2011.…”
Section: Accidents and Injuriesmentioning
confidence: 99%
“…They found that motor vehicle crashes did not increase during Ramadan. 24 Also, Khammash and Al-Shouha enrolled all patients with an road traffic accident-related diagnosis in the ED of Princess Basma Teaching Hospital, Irbid, Jordan, during and around Ramadan. They found no significant differences between the numbers and severity of injuries among the subgroups of patients concerning the time of the day or the weekdays.…”
Section: Accidents and Injuriesmentioning
confidence: 99%